P34. Configuration, validation and evaluation of the dose calculation algorithm Acuros XB. (December 2016) - Birba, I.; Zefkili, S.; Bernard, L.
Abstract : Purpose: The purpose of this study is to implement dosimetric data libraries in a dose calculation algorithm Acuros XB (developed by Varian) in a treatment planning system, to validate the libraries and evaluate the performances of the algorithm with several tests in order to be used in the radiotherapy department. Materials and Methods: Acuros XB (AXB) is implanted in the Eclipse TPS Version 10. The methodology used is that of the ESTRO booklet n°7 for the calculation of dose and monitor units (MU) with several levels of tests (level 1, 2 and 3 for static techniques, non-IMRT photon beams and one test with RapidArc technique). Level 1 tests assess AXB in simple configurations (square, rectangular fields) in absolute and relative dose, level 2 tests verify the accuracy consideration of beams modifiers (wedge filters, asymmetric fields), Level 3 tests, using the quality index methodology assess the modeling of the dose distribution with heterogeneity and scatter dose (small complex fields, thin central block) for 6 and 15 MV. Finally a test assesses AXB performances in a complex configuration (small fields, variation of dose rate, MLC movement) with the RapidArc technique. Dose calculations made by AXB on the Eclipse TPS are comparing to measurements which are the references in the same conditions. The tolerances fixed are those presented in the reports of the ESTRO 7 (static techniques, non-IMRT) and ESTRO 9 (IMRT and RapidArc). Main Results and Discussion: The calculations made by AXB are in agreement with the measurements for all tests level. Some differences are observed, their number is nevertheless low. Differences between the calculations and measurements are observed at the interface water–air interface; however, they are less important than those observed in AAA and PBC. Conclusion and Discussion: Acuros XB models and calculates accurately the dose in simple configurations, with modifiers beams, and with the presence of heterogeneities for static irradiation techniques, and also with a more complex configuration with the RapidArc technique. Acuros XB can be used as a dose calculation algorithm in the Eclipse TPS at the radiotherapy department of the Institut Curie Paris.